IslamicâIranian Identity from the Perspective of Chaos and Complexity Theory - Sayed Vali Moosavinejad (جامعه شناسی کاربردی, 2014)
Introduction In today's world having multiple identities, national, local, international, religious, occupational, gender, professional, group, tribal, linguistic and so on is a part of the requirements of social life. This paper seeks to investigate the elements formulating Islamic-Iranian identity in the current period. This period has experienced strong progress in all aspects of science, art, and literature, which has in turn brought about new needs and problems. What is clear is the fact that with the advent of the twentieth century and its idiosyncrasies, human beings appear to be bewildered, frustrated, alienated from themselves. Philosophers, intellectuals and ordinary people are confronted with a state of confusion, asking themselves: Who am I? What am I? Why am I here? With an understanding of the complexity of multiple identities, the big question that remains is: What factors affect the Islamic Identity in the present period and how these elements contribute to formulation, prosperity, and decline of this identity? In reply to this question, we put this hypothesis to the test: Islamic Iranian identity under the influence of various interactive elements and numerous actors will be organized through self-organizing and its injuries are treated through self-healing.